Karakteristik dan Pola Kampung Nelayan - Muhammad Aldi Rahmatul Hakim; Laretna Trisnandari; Ikaputra - (Unika Soegijapranata Semarang, 2019)
This study uses a literature review to explain the characteristics and patterns of fishing villages. In some literature, it is known that a pattern of Fishermen's villages arises because of the same behavior pattern, the majority of which depend on income from fishing. Many studies explain that fishermen make the Sea a dominant factor in earning income, but seasonal fishermen work causes fishermen to have alternative income from other sectors, whether or not related to the sea. The culture of the fishermen provides a characteristic for the form of single occupancy and in the village scale, in several studies showing the form of single occupancy of fishermen reflects a need, and adaptation to nature as a form of disaster response. Single occupancy of fisherman has the characteristic of a veranda that functions as a family gathering place or as a place to repair nets and warehouses that serve to store equipment. The characteristic sediment in the village scale, the Fishermen's village is oriented to the sea, and in the village facilities are the availability of boat berths for ship stops, as well as the availability of Tempat Pelelangan Ikan (TPI) to facilitate the sale and purchase transactions of the sea. Other supporting factors that support village life are infrastructure and public facilities, infrastructure related to roads, drainage, clean water and electricity, while public facilities consist of schools and places of worship. The linkages between village components make an identity of a fisherman village.